Examining the Role of Depression Levels of University Students on Social Media Addiction in the COVID-19 Outbreak: A Structural Equation Model - Dikmen, Melih (Erkan MOR, 2021)
Objective: The purpose of this study is to examine the relationship between the depression levels of university students and their social media addiction in the COVID-19 pandemic through structural equation modeling. Method: The research was conducted according to the relational survey model, one of the quantitative research methods. The research was carried out on 211 university students at Firat University. Burns Depression Scale, adapted into Turkish by Tuncer and Dikmen (2019), was used to determine the depression levels of students. Social Network Addiction Scale developed by Karaca, Yıldırım and Kulaksız (2019) was used to determine the social media addiction levels of the students. Results: When the findings of the study are examined, it is seen that there are significant relationships between depression level and social media addiction. A good fit was found between the obtained data and the predicted model. In this context, it has been determined that the depression levels of university students in the COVID-19 pandemic are the predictors of social media addiction. It has been observed that as the depression levels of university students increase, their social media addiction increases. Conclusion: It can be said that depression and social media addiction form a spiral structure that negatively affects each other. In this context, the concept of depression in social media addiction can be seen as a cause or a consequence.

Amaç: Bu araştırmanın amacı COVID-19 pandemisinde üniversite öğrencilerinin depresyon düzeyleri ile sosyal medya bağımlılıkları arasındaki ilişkiyi yapısal eşitlik modellemesiyle incelemektir. Yöntem: Araştırma nicel araştırma yöntemlerinden ilişkisel tarama modeline göre yürütülmüştür. Araştırma Fırat Üniversitesindeki 211 üniversite öğrenci üzerinde gerçekleştirilmiştir. Öğrencilerin depresyon düzeylerini belirlemek amacıyla Tuncer ve Dikmen (2019) tarafından Türkçeye uyarlanan Burns Depresyon Ölçeği kullanılmıştır. Öğrencilerin sosyal medya bağımlılık düzeylerinin belirlenmesi amacıyla ise Karaca, Yıldırım ve Kulaksız (2019) tarafından geliştirilen Sosyal Ağ Bağımlılığı Ölçeği kullanılmıştır. Bulgular: Araştırmanın bulguları incelendiğinde depresyon düzeyi ve sosyal medya bağımlılığı arasında anlamlı ilişkiler olduğu görülmektedir. Elde edilen veri ile öngörülen model arasında iyi uyum saptanmıştır. Bu bağlamda üniversite öğrencilerinin COVID-19 pandemisindeki depresyon düzeylerinin sosyal medya bağımlılıklarının yordayıcısı olduğu belirlenmiştir. Üniversite öğrencilerinin depresyon düzeyleri arttıkça sosyal medya bağımlılıklarının arttığı gözlemlenmiştir. Sonuç: Depresyon ve sosyal medya bağımlılığının birbirini olumsuz yönde etkileyen sarmal bir yapıyı oluşturduğu söylenebilir. Bu bağlamda sosyal medya bağımlılığında, depresyon kavramı bir sebep olabileceği gibi bir sonuç olarak da görülebilir.
COVID-19 Pandemisinde Üniversite Öğrencilerinin Depresyon Düzeylerinin Sosyal Medya Bağımlılığı Üzerindeki Rolünün İncelenmesi: Bir Yapısal Eşitlik Modeli
Keywords: Behaviour-Personality Assessment in Psychology; Psikolojide Davranış-Kişilik Değerlendirmesi